2002
DOI: 10.1136/bjo.86.2.185
|View full text |Cite
|
Sign up to set email alerts
|

The Auckland Cataract Study: co-morbidity, surgical techniques, and clinical outcomes in a public hospital service

Abstract: Aim: To prospectively assess cataract surgery in a major New Zealand public hospital by defining presenting clinical parameters and surgical and clinical outcomes in a cohort of subjects just below threshold for treatment, based upon a points based prioritisation system. Methods: The prospective observational study comprised 488 eyes of 480 subjects undergoing consecutive cataract operations at Auckland Hospital. All subjects underwent extensive ophthalmic examination before and after surgery. Details of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
105
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 22 publications
17
105
1
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][27][28][29]37,38 However, the prevalence of patients' systemic co-morbidities, without grouping them as a health status index, is rarely described in such series. 30,37,38 These co-morbidities could have been overrepresented among our patients (Table 1) because of our hospital being a tertiary one, which seems to be the case in the Auckland cataract study 38 too; in fact, in population cataract studies 2 or in those studies involving several settings 37,39 a lower rate of some systemic comorbidities was obtained. Our higher prevalence of systemic co-morbidities in men (Table 1) could introduce some bias in our results.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][27][28][29]37,38 However, the prevalence of patients' systemic co-morbidities, without grouping them as a health status index, is rarely described in such series. 30,37,38 These co-morbidities could have been overrepresented among our patients (Table 1) because of our hospital being a tertiary one, which seems to be the case in the Auckland cataract study 38 too; in fact, in population cataract studies 2 or in those studies involving several settings 37,39 a lower rate of some systemic comorbidities was obtained. Our higher prevalence of systemic co-morbidities in men (Table 1) could introduce some bias in our results.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] For these reasons we study the preoperative conjunctival bacteria of patients undergoing cataract surgery at different stages of age. These bacteria are the main source of contamination of intraocular surgery, 16,17 and it is possible that sometimes bacteria produce inflammation that could be treated without developing infectious postsurgical endophthalmitis; but it could damage ocular tissues as well.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively similar proportions of patients with (80.2%) and without (88.8%) preoperative ARM The proportions of our patients with and without ARM achieving VAZ6/12, 1-3 years after surgery, were similar to previously reported short-term cataract surgery visual outcomes. 2,12,[28][29][30] Using this same cohort, we previously reported that 82% of persons with ARM achieved VAZ6/12, 4 weeks after surgery. 24 Several studies have reported short-term (up to 1 year) postoperative best-corrected VA. 2,12,28,29 In general, VAZ6/12 was achieved overall in 90% of eyes, and in 95% of eyes without pre-existing ocular disease.…”
Section: Discussionmentioning
confidence: 88%
“…2,12,[28][29][30] Using this same cohort, we previously reported that 82% of persons with ARM achieved VAZ6/12, 4 weeks after surgery. 24 Several studies have reported short-term (up to 1 year) postoperative best-corrected VA. 2,12,28,29 In general, VAZ6/12 was achieved overall in 90% of eyes, and in 95% of eyes without pre-existing ocular disease. In the Auckland Cataract Study cohort of 97 patients aged 76.3 (79.9) years, randomly selected from 480 participants, 95% of eyes maintained a bestcorrected VAZ6/12, 2 years after surgery.…”
Section: Discussionmentioning
confidence: 88%